Design and Implementation of Derivation Cryptographic Algorithms in Embedded Contactless IC Card System - Li, Ping; Fang, Xiang Qun; Ge, Hai Bo (Applied Mechanics and Materials, 2012)
The paper studied the security measures of contactless IC card system. Derivation cryptographic algorithms were used in the embedded IC card system to generate multi-application cipher key, providing an effective solution for the applications with high security requirements.